2x-10y+7=0

Simple and best practice solution for 2x-10y+7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-10y+7=0 equation:


Simplifying
2x + -10y + 7 = 0

Reorder the terms:
7 + 2x + -10y = 0

Solving
7 + 2x + -10y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 2x + -7 + -10y = 0 + -7

Reorder the terms:
7 + -7 + 2x + -10y = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 2x + -10y = 0 + -7
2x + -10y = 0 + -7

Combine like terms: 0 + -7 = -7
2x + -10y = -7

Add '10y' to each side of the equation.
2x + -10y + 10y = -7 + 10y

Combine like terms: -10y + 10y = 0
2x + 0 = -7 + 10y
2x = -7 + 10y

Divide each side by '2'.
x = -3.5 + 5y

Simplifying
x = -3.5 + 5y

See similar equations:

| 35=11y+2 | | .5(6x-3)=.5(6+6x) | | -(7x+10)-10=-8(4+x) | | 2(c+6)=3G-6g | | x=3x-40 | | 7b=10b+18 | | 6(-10p-3)-8p=6(-12p-3)-4 | | v^2-4v-37=2 | | 24x-3(2x-5)=51 | | 73-x=86-2x | | (2x^2-3xy^2-y^2)-(3x^2-xy^2)= | | F(X)=20(0.9)x^6 | | 6m+9+7x-2= | | 9.25x=5.75x+40 | | 8w-12=(-4) | | -10+6m-m=-1+3m+5m | | 74t+28t-101t+16=89 | | 3n-6=3-5n-n | | 5+7-9-8=11 | | -4(w+1)=-20 | | -7y+14=-28 | | 5x^2+4x=-3 | | 4x-10=3x-4 | | -540+13p=1500 | | -67a+56a=99 | | 4n^2=256 | | 4x-30=130 | | 37a-73a+73a+-33a=100 | | -2a-2=0 | | 5x-5.5=5x+26 | | x^2y+2xy-4x+y=0 | | 9c+13=58 |

Equations solver categories